Physical Symptoms, Unmet Needs, and Quality of Life in Thai Cancer Survivors after the Completion of Primary Treatment - Kanaungnit Pongthavornkamol; Pichitra Lekdamrongkul; Pimchan Pinsuntorn; Alex Molassiotis (Elsevier, 2019)
Objectives: This study investigated physical symptoms, unmet supportive care needs, and quality of life (QoL) perception among different types of Thai cancer survivors who had completed first-line treatment. Methods: A cross-sectional study recruited breast, gynecological, colorectal, lung, and head and neck cancer survivors (n = 236) who were attending follow-up visits at a regional cancer hospital in central Thailand. Data were collected by the Physical Symptom Concerns Survey, the Cancer Survivors' Unmet Needs Scale, and a single item measuring global QoL. Descriptive statistics, one-way analysis of variance (ANOVA), and Welch's ANOVA were used for data analysis. Results: Cancer survivors generally perceived good QoL, with significantly low QoL for lung cancer survivors (P < 0.001). There were no differences in symptom experiences among the five cancer groups, except for pain, which was significantly higher in lung cancer survivors than in the other four groups. The most frequently reported symptoms across all groups were numbness in the hands/feet, sleep disturbances, fatigue, and pain. The top unmet supportive care need among all participants was related to concerns of cancer recurrence (44.5%). Head and neck cancer survivors reported the highest number of unmet needs among the five cancer groups. Conclusions: This study mapped the unmet supportive care needs in Thai cancer patients and showed that patients with head and neck cancer and lung cancer were strongly affected. A survivorship care plan focusing on managing physical symptoms and providing supportive and psychosocial care should be developed to meet the needs of each cancer survivor group and to enhance QoL after the completion of treatment.